2021
DOI: 10.3390/biology10090858
|View full text |Cite
|
Sign up to set email alerts
|

Retinol-Binding Protein-4—A Predictor of Insulin Resistance and the Severity of Coronary Artery Disease in Type 2 Diabetes Patients with Coronary Artery Disease

Abstract: (1) Background: Insulin resistance (IR) is the fundamental cause of type 2 diabetes (T2D), which leads to endothelial dysfunction and alters systemic lipid metabolism. The changes in the endothelium and lipid metabolism result in atherosclerotic coronary artery disease (CAD). In insulin-resistant and atherosclerotic CAD states, serum cytokine retinol-binding protein-4 (RBP-4) levels are elevated. The adipocyte-specific deletion of glucose transporter 4 (GLUT4) results in higher RBP-4 expression and IR and athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…A U-shaped association has been described between RBP4 level and the incidence of T2DM [ 41 , 42 ]; however, Schiborn et al mentioned that this association was detected only in women [ 42 ]. A Thai study showed that high circulating RBP4 was a predictor of insulin resistance and the severity of coronary artery disease (CAD) in T2DM with CAD [ 43 ]. However, it must be noted that Asian race, lower BMI (~25 kg/m 2 ), severe comorbidities, i.e., CAD, and intensive insulin therapy can shade these results and make it difficult to compare them with our data.…”
Section: Discussionmentioning
confidence: 99%
“…A U-shaped association has been described between RBP4 level and the incidence of T2DM [ 41 , 42 ]; however, Schiborn et al mentioned that this association was detected only in women [ 42 ]. A Thai study showed that high circulating RBP4 was a predictor of insulin resistance and the severity of coronary artery disease (CAD) in T2DM with CAD [ 43 ]. However, it must be noted that Asian race, lower BMI (~25 kg/m 2 ), severe comorbidities, i.e., CAD, and intensive insulin therapy can shade these results and make it difficult to compare them with our data.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that there is a correlation between the concentration of free RBP and the thickness of intima media, a diagnostic indicator of carotid artery atherosclerosis [ 25 ]. In addition, the concentration of RBP4 in the blood is associated with cardiovascular risk factors associated with insulin resistance and CHD, circulating RBP4 can be a marker of metabolic complications and atherosclerosis and used to assess CHD [ 26 , 27 ]. In early studies, we found an increase in the levels of transthyretin transport proteins and RBP4 in the blood of patients with coronary atherosclerosis compared with controls [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 Meanwhile, extensive epidemiological studies have demonstrated that RBP4 is a circulating biomarker of insulin resistance and the risk of cardiovascular disease and metabolic syndrome. [31][32][33] In 2021, Chauhan et al further proved that RBP4 could be used as an early evaluation indicator of type 2 diabetes and was linearly correlated with HOMA-IR. With increased serum RBP4 level of 1 mg/L, HOMA-IR increased significantly by 0.007 units.…”
Section: Epicardial Adipose Tissue and Diabetes Mellitusmentioning
confidence: 99%